On A Simple Construction Of Triangle Centers X(8), X(197), X(K) & X(594) - Dasari Naga Vijay Krishna (Scientific Inquiry and Review, 2018)
In this article, we provide a new method for constructing the Nagel Point{X(8)} , Cevian quotient of Symmedian Point, Nagel Point {X(197)} and the isogonal conjugate of 1st Hatzipolakis-Yiu Point{X(594)}. In addition, we also establish some collinearity and concurrence.